The Effect of Accrual Earnings Management and Real Earnings Management on Environmental, Social, and Governance (ESG) Reporting Performance - Fadhilah, Alfiyyah Nuur; Suranta, Eddy (Yayasan Ilomata, 2024)
This research aims to offer empirical insights into variations in earnings management within companies categorized in the Environmental, Social, and Governance (ESG) score ranking, and seeks to establish a correlation between earnings management practices and Environmental, Social, and Governance (ESG) performance. The study scrutinizes accrual earnings management alongside real earnings management. The Environmental, Social, and Governance (ESG) score ranking comprises four categories: low, medium, high, and severe. Accrual earnings management is gauged through the modified Jones model, while real earnings management is assessed using three proxies ABNCFO, ABNPROD, and ABNDISC. The research focuses on manufacturing companies possessing Environmental, Social, and Governance (ESG) scores and adopts a purposive sampling approach. The outcomes reveal distinctions between ABNCFO and ABNPROD real earnings management in the severe and low ESG rating groups, whereas no differences exist in accrual earnings management and ABNPROD real earnings management. Additionally, the study establishes that ABNCFO and ABNDISC real earnings management significantly influence Environmental, Social, and Governance (ESG) performance positively. Conversely, accrual earnings management shows no adverse impact on Environmental, Social, and Governance (ESG) performance, and ABNPROD real earnings management exhibits a positive albeit insignificant effect on Environmental, Social, and Governance (ESG) performance. The practical implication of this research is that when the company has a high ESG score which reflects the uncertainty of the company's future operations, the company tends to carry out real earnings management in the form of abnormal cash flow operations (ABNCFO) and abnormal discretionary expenses (ABNDISC).